The vision of the neighbours' associations on their community function and the degree of integration in other actions in the territory. A case study from their self-assessment - Vecina Merchante, Carlos; Calvo Sastre, Aina (Cuadernos de Trabajo Social, 2024)
During the end of Franco's regime and the first years of democracy in Spain, neighbourhood associations (NA) acquired a fundamental role in community political and social action, leading the demand for improvements in peripheral neighbourhoods (Castells, 2001; Gutiérrez, 2016). Currently, these associations have lost some of their strength, coinciding with a crisis of the traditional model of participation (Alberich, 2022). This research focuses on an area of Palma (Balearic Islands-Spain) prioritised by the Social Services to implement a community intervention project. Using qualitative methods such as focus groups and semi-structured interviews, the aim is to identify the current state of the NA in this area, to find out about their social role, whether there is an existing network of associations, the level to which they are integrated into it and whether they maintain a traditional community approach. The results show the vision of the NA about their role in the community, the attitude of the citizens, their participation and the relationship of the NA with the institutions and other community agents. Different degrees of integration in the new community context appear; in which the diversity of collectives, interests and ways of participation may be an opportunity to recover their protagonism or, on the contrary, further weaken their role, due to the inability to adapt to current changes.
Keywords: Neighbourhood associations; community development; citizen participation; social capital